Learning models innovation in industrial revolution 4.0 era - Metsa Fajrianti Kusumah Suwandi; Muhammad Alfat (Curricula)
The era of the Industrial Revolution 4.0 has created a shift in every dimension of life, one of which is the education dimension. In anticipating the rapid transformation that is taking place, education must always develop its competence and academic innovation. This study aims to analyze the education that occurs, the learning models used, as well as the innovative curriculum set in the era of the Industrial Revolution 4.0. The method used in this research is the literature study method. The data generated using this method were re-analyzed through the stages of reading and recording data as research material to processing the research materials. The study results show that the Industrial Revolution 4.0 era resulted in changes in human life patterns due to the influence of technological devices. This change underlies the design and establishment of a new innovative curriculum that is in accordance with the 4.0 revolution era. The 2013 curriculum as a complement to the previous curriculum is here to make education accustomed to the use of technological devices. Education as a place to educate the nation's successors needs to keep up with all the changes that occur so that learning can be obtained by students who are not left behind from the latest information.